Abordagem clínica e laboratorial sobre um caso de septicemia por Candida parapsilosis em um neonato com onfalocele - Pereira, Simone Santana (2016)
: The omphalocele is a malformation where there is a herniation of abdominal contents in the cord insertion point. One of the main problems associated with this anomaly is that the neonate undergoing surgical procedures in the early days of life, which ends up prolonging his hospitalization and increasing the risk of infection by opportunistic microorganisms. In this context, infection by Candida species have been assigned the risk factors, such as long-term administration of broad-spectrum antibiotics, abdominal surgeries and diagnostic procedures, and the species Candida parapsilosis is more closely related to the cases of neonatal infection due to its ability of adhesion and form biofilms. The aim of this study was to increase knowledge of the clinical and microbiological approach to sepsis by C. parapsilosis in a case of a neonate. A descriptive study with retrospective approach of a neonate who underwent surgery in early life due to omphalocele was conducted. This work was divided into two stages: focused on the description and outcome of the case; and related to virulence factors of C. parapsilosis from neonate. For the development work was carried out the neonate records survey according to the Ethics Committee of the Universidade Estadual de Maringa approval No 615643. Yeasts were isolated from blood, urine, and central venous catheter and identified by classic and MALDI-TOF MS method. They evaluated factors such as susceptibility to antifungal agents, adhesiveness, biofilm formation, influence of the biofilm antifungal and genetic similarity among clinical isolates in the front hospitalization to various therapeutic attempts. C. parapsilosis was able to cause sepsemia in the neonate even under antifungicoterapia administration, the case evolved with sepsis from 28 days of life until death after 102 days. The total of 16 isolates showed high capacity of adherence, tolerance micafungin and independent of the collected period and sample treated in the same yeast, stressing the importance of bloodborne infection by C. parapsilosis in neonates exposed to multiple risk factor. .